PENGGUNAAN KAPUR TOHOR (CaO) DALAM PENURUNAN KADAR LOGAM Fe DAN Mn PADA LIMBAH CAIR PEWARNAAN ULANG JEANS KABUPATEN MAGELANG TAHUN 2017 - Neni Saswita; Sulistyani Sulistyani; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2018)
The industry of recoloring jeans used pigment in the process of fabrication produces liquid waste containing Fe that  was 23.90 mg/l, Mn is 35.18 mg/l that exceeded the threshold according to Central Java Provincial Regulation No. 5 of 2012 about Waste Water Quality Standard for Fe that was 5 mg/l and Mn was 2 mg/l. Waste water that was not in accordance with the quality standard can cause environmental damage and health. The usage of calcium oxide with coagulation-flocculation method is one of the technologies used to decrease the liquid waste metal content. The purpose of this research was to know the use of calcium oxide to decrease metal content of Fe and Mn toward liquid waste recoloring jeans at Magelang district. The type of this research was  true experimental of pretest and posttest with control group design. Sample of this research wasted water of recoloring jeans at Magelang district. Data analysis with Shapiro Wilk test (p≤ 0.05). The result shown early content of Fe was 0.805 mg/l and the content of Mn was 4.188 mg/l. The average pH and temperature of liquid waste before treatment was 11 and 28.02°C. After treatment the pH and temperature of calcium oxide 4 gr was 11 and 28.47°C then it was 11 and 28.44°C for calcium oxide 5 gr. There was decreasing metal content with distributing calcium oxide 4 gr as 13.7% for Fe and 27% of Mn, meanwhile the decreasing for calcium oxide  5 gr was 30.7% for Fe and 28.2% for Mn. Shapiro Wilk test shown 0.0001 (p≤0.05) which means there was a different decrease of metal content of Fe recoloring jeans with various dose treatment of calcium oxide. Instead  for metal content of Mn that shown 0.171 (p≥0.05) which means there was no difference decrease of metal content of Mn recoloring jeans with various dose treatment of calcium oxide.